The diffusion of foreign divestment from Burma - Soule, Sarah A.; Swaminathan, Anand; Tihanyi, Laszlo (Strategic Management Journal, 2014)
We examine variation in the rate of divestment by multinational firms from B urma. We argue that in addition to a set of firm‐level characteristics known to impact divestment decisions, firms are also influenced by characteristics of their home country and the divestment patterns of others. Using data on firms operating in B urma during 1996–2002, we model these multiple influences on firms to divest. Our results show that beyond firm‐level concerns, firms divest in response to the political characteristics of their home country, including protest, the level of political freedom, and transparency of institutions. We also find that the centrality of their home country in the network of intergovernmental organizations impacts divestment patterns in interesting ways. Copyright © 2013 John Wiley & Sons, Ltd.